2011
DOI: 10.1186/1471-2458-11-936
|View full text |Cite
|
Sign up to set email alerts
|

Giving offspring a healthy start: parents' experiences of health promotion and lifestyle change during pregnancy and early parenthood

Abstract: BackgroundThere are good opportunities in Sweden for health promotion targeting expectant parents and parents of young children, as almost all are reached by antenatal and child health care. In 2005, a multisectoral child health promotion programme (the Salut Programme) was launched to further strengthen such efforts.MethodsBetween June and December 2010 twenty-four in-depth interviews were conducted separately with first-time mothers and fathers when their child had reached 18 months of age. The aim was to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
130
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(148 citation statements)
references
References 46 publications
14
130
2
2
Order By: Relevance
“…This knowledge suggests that health agencies should develop policies and programs to support the maintenance of healthy behaviour in women after their children have grown or have left the household, or after disruption of a partnership. Furthermore, a more gender-equal focus in health promotion might increase men's involvement in lifestyle change (Edvardsson et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…This knowledge suggests that health agencies should develop policies and programs to support the maintenance of healthy behaviour in women after their children have grown or have left the household, or after disruption of a partnership. Furthermore, a more gender-equal focus in health promotion might increase men's involvement in lifestyle change (Edvardsson et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Viau et al expressed that women experience worries related to the health of fetus, changes in daily activities, risks related to pregnancy such as abortion and social commitment during their pregnancy (31). Various studies on women implied fetal health was the most important motivating factor for making changes in the lifestyle (31,33,34). Addicted women's reasons to change their lifestyle were concerns about the health of the fetus and newborn, loving children and belief that they deserved to have the chance for a healthy life.…”
Section: Behavioral Changes In Pregnancymentioning
confidence: 99%
“…Addicted women's reasons to change their lifestyle were concerns about the health of the fetus and newborn, loving children and belief that they deserved to have the chance for a healthy life. Therefore, they were too eager to get health-related messages to improve neonatal outcomes (33). On the other hand, studies suggested that pregnant women were not informed enough concerning the issues related to health (33,35), so they were unable to express the benefits of changing the diet and physical activities (35), plus they did not have sufficient information about obesity and overweight (33,35).…”
Section: Behavioral Changes In Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…We know that parents change their lifestyle habits at pregnancy recognition to ensure the health of the fetus [44]. Pregnancy is a window of opportunity through which health-promoting interventions can be applied, since parents are generally open to change at that time.…”
Section: Discussionmentioning
confidence: 99%